Abundance of Whales in West and East Greenland in Summer 2015 - Hansen, Rikke Guldborg; Boye, Tenna K.; Larsen, Rasmus S.; Nielsen, Nynne H.; Tervo, Outi; Nielsen, Rasmus D.; Rasmussen, Marianne H.; Sinding, Mikkel H. S.; Heide-Jørgensen, Mads Peter (NAMMCO Scientific Publications, 2018)
An aerial line transect survey of whales in West and East Greenland was conducted in August-September 2015. The survey covered the area between the coast of West Greenland and offshore (up to 100 km) to the shelf break and in East Greenland from the coast up to 50 km offshore crossing the shelf break. A total of 423 sightings of 12 cetacean species were obtained and abundance estimates were developed for common minke whale, (Balaenoptera acutorostrata), fin whale (Balaenoptera physalus), humpback whale (Megaptera novaeangliae), harbour porpoise (Phocoena phocoena), long-finned pilot whale, (Globicephala melas) and white-beaked dolphin (Lagenorhynchus albirostri). The estimates were corrected for perception bias and availability bias where possible. Data on surface corrections for minke whales and harbour porpoises were collected from whales instrumented with satellite-linked time-depth-recorders. Options for estimation methods are presented and the preferred estimates are: minke whales: 5,095 (95% CI: 2,171-11,961) in West Greenland and 2,762 (95% CI: 1,160-6,574) in East Greenland, fin whales: 2,215 (95% CI: 1,017-4,823) in West Greenland and 6,440 (95% CI: 3,901-10,632) in East Greenland, humpback whales: 993 (95% CI: 434-2,272) in West Greenland and 4,223 (95% CI: 1,845-9,666) in East Greenland, harbour porpoises: 83,321 (95% CI: 43,377-160,047) in West Greenland and 1,642 (95% CI: 319-8,464) in East Greenland, pilot whales: 9,190 (95% CI: 3,635-23,234) in West Greenland and 258 (95% CI: 50-1,354) in East Greenland, white-beaked dolphins 15,261 (95% CI: 7,048-33,046) in West Greenland and 11,889 (95% CI: 4,710-30,008) in East Greenland. The abundance of cetaceans in coastal areas of East Greenland has not been estimated before, but the limited historical information indicates that the achieved abundance estimates were remarkably high. Comparing the estimates from 2015 in West Greenland with a similar survey conducted in 2007, there is a trend towards lower densities in 2015 for the baleen whale species and white-beaked dolphins. Harbour porpoises and pilot whales, however, did not show a similar decline. The decline in baleen whale and white-beaked dolphin abundance is likely due to emigration to the East Greenland shelf areas where recent climate driven changes in pelagic productivity may have accelerated favourable conditions for these species.
Keywords: surveys; marine mammals; whales; North Atlantic; abundance; Greenland; cetaceans; trends; aerial surveys